Improved mental health outcomes and normalised spontaneous EEG activity in veterans reporting a history of traumatic brain injuries following participation in a psilocybin retreat - Blest-Hopley, Grace; Pasculli, Giuseppe; Ruffell, Simon G. D.; Tsang, WaiFung; Emmanuel, Olateju; Pate, Kathryn M.; Kettner, Hannes; Roseman, Leor; Erritzoe, David; Carhart-Harris, Robin (Frontiers in Psychiatry, 2025)
IntroductionPsilocybin, a serotonergic psychedelic, has shown therapeutic potential in treating mental health disorders by, amongst the many effects, promoting neuroplasticity and reorganising functional connectivity across cortical and subcortical networks involved in emotion and cognition. Veterans with traumatic brain injuries (TBI) often experience chronic neurological and psychological symptoms such as post-traumatic stress disorder (PTSD) and depression. This study investigates the effects of psilocybin administered in retreat settings on veterans with a history of TBI, focusing on mental health outcomes and changes in brain connectivity as measured by EEG.MethodsA total of 21 participants were recruited through the Heroic Hearts Project, which facilitated access to two six-day psilocybin retreats in Jamaica. Before the retreat, participants underwent three individual and three group coaching sessions to prepare for the experience. During the retreat, two psilocybin ceremonies were held, spaced 48 hours apart. Participants received an initial dose of 1.5g to 3.5g of dried psilocybin mushrooms, with the option to increase the second dose up to 5g. Psilocybin was administered in a tea format, under the supervision of experienced facilitators. Psychological outcomes were assessed using validated questionnaires (PCL-5, PHQ-9, STAI) at baseline (four weeks pre-retreat) and four weeks post-retreat. Electroencephalography (EEG) was used to measure brainwave activity pre- and post-treatment. Paired t-tests were used to analyze changes in psychological scores, while EEG frequency band analysis assessed changes in brain function and connectivity.ResultsImprovements were observed across several mental health measures: PTSD (PCL-5 scores decreased by 50%, p=0.010), depression (PHQ-9 scores decreased by 65%, p<0.001), and anxiety (STAI) scores decreased by 28%, p<0.001). EEG data showed decreased delta and theta power in frontal and temporal regions, indicating potential improvements in cognitive control and emotional processing. Enhanced coherence in alpha and beta bands suggested improved neural communication.DiscussionThe study suggests that psilocybin retreats might provide improvements in psychological well-being and brain connectivity in veterans with TBI. Reduced delta power and normalised theta activity suggest better emotional regulation, while improved coherence in alpha and beta bands may reflect increased cognitive engagement. Further, these preliminary outcomes provide a potential rationale for the design and implementation of larger-scale, controlled studies to validate and expand upon these initial findings.